Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Terhadap Pembelian Ayam Pecak Buk Ana Di Gampong Blang Paseh, Kecamatan Langsa Kota, Kota Langsa - Akmal, Dzaky; Anzhita, Silvia; Mastuti, Rini (Jurnal Penelitian Agrisamudra, 2025)
This study aims to analyze the factors that influence consumer satisfaction towards purchasing Ayam Pecak Buk Ana in Gampong Blang Paseh, Langsa Kota District, Langsa City. The sampling method used is nonprobability sampling in the form of accidental sampling with a sample size of 96 people. To see the effect of price (X1), product quality (X2), service quality (X3), and location (X4) on the variable (Y) on purchasing Ayam Pecak Buk Ana in Gampong Blang Paseh, Langsa Kota District, Langsa City, the author uses the multiple linear regression method. Data analysis was carried out using SPSS 21 computer software. Based on the results of the simultaneous test (F Test) it shows that all independent variables of price (X1), product quality (X2), service quality (X3), and location (X4) together have a significant effect on the dependent variable (Y) of consumer satisfaction. Based on the partial test results (t-test), it shows that each of the independent variables, price (X1), product quality (X2), service quality (X3), and location (X4), have a significant effect on the dependent variable (Y) of consumer satisfaction.